Sensitivity prediction analysis of the contribution of physical fitness variables on Terengganu Malaysian youth archers’ shooting scores - Mohamad Razali, Abdullah; Pathmanathan, K. Suppiah; Rabiu Muazu, Musa; Kiet, Tomny Wong Kee; Ahmad Bisyri Husin, Musawi Maliki; Norlaila Azura, Kosni; Mainul, Haque (2017)
Successful performance in archery may require certain physical fitness attributes due to the long hours it takes during both training and competition. It is essential, therefore, to determine the actual role physical fitness variables could play on the shooting performance of the archers. This study aims to explore the role of physical fitness variables on the shooting performance of youth archers as well as to predict the discriminating fitness variables that can play a significant role in archery performance. A total number of 16 youth archers with mean age 14.6 participated in the study. Standard physical fitness measurements were carried out prior to their shooting practice, and a simulated shooting competition area was set up, and all the archers’ shot 12 arrows over a distance of 50 meters. Standard linear multiple regression was employed to predict the association between the shooting scores (DV) with the physical fitness variables (IVs). A significant regression equation was obtained F (8, 7) = 6.40, p < 0.05, R2 = 0.88 indicating that the model accounted for approximately 88% variability of the whole data set. Sensitivity prediction analysis of the contributions of the best model after leave-one-out method revealed that handgrip has the highest contribution in the model while standing broad jump has a low contribution in the entire model. However, correlations were found between the DV and muscle strength, handgrip, leg power and balance, r = 0.60, 0.55, 0.31 and 0.74 respectively.